Robust Filtering for Linear Equality Constrained Systems - Chuanbo Wen; Yunze Cai; Xiaoming Xu (Discrete Dynamics in Nature and Society)
This paper deals with the robust filtering problem for linear discrete-time constrained systems. The purpose is the design of a linear filter such that the resulting error system is bounded. An orthogonal factorization is used to decompose the original robust filtering problem into stochastic and deterministic parts, which are then solved separately. Finally, a numerical example is presented to demonstrate the applicability of the proposed method.